The Effect of COVID-19 on The Chinese Restaurant Industry and The Role That Third-Party Food Delivery Businesses Played in Helping Restaurants Respond to The Crisis - He, Jiexue (Auckland University of Technology, 2021)
The outbreak of the COVID-19 coronavirus in Wuhan, China, in January 2020 has had an unprecedented impact on the tourism, hotel and catering industry globally. The aim of this research is to explore the impact of COVID-19 pandemic on the Chinese restaurant industry and the role that the third-party food delivery platform companies played in helping the restaurants respond to the pandemic crisis. This study first reviewed the past pandemic crises and summarized their impacts on aspects of health and finance, then utilized the document analysis method within a qualitative research process to collect data. Four themes came through the thematic analysis: 1) the impact of COVID-19 on the Chinese restaurant industry (with restaurant cashflow being the most affected); 2) the most important measure in response to the restaurant's cashflow crisis was to increase revenue and reduce expenditure; 3) the influence of the takeout business model in traditional restaurants' response to COVID-19; and 4) the effect of third-party delivery platforms in helping restaurants cope with the COVID-19 crisis. The research findings revealed that, although SARS and COVID-19 have similar biological structures and modes of transmission, the impact of COVID-19 on the restaurant industry was far greater than that of SARS. Moreover, during the epidemic period, the third-party food delivery platforms launched a variety of measures to actively respond to COVID-19, such as providing contactless services and cooperating with restaurants to develop "peace in mind" reassurance programs, effectively helping restaurants to increase the number of customers, takeout, and food delivery orders. This research concluded that the third-party food delivery platform played a positive role in helping the Chinese restaurant industry respond to the COVID-19 crisis.
Keywords: COVID-19; Pandemic crisis; Full-service; Chinese restaurant industry; Takeaway; Food delivery